Association Between Socio-Demographic Characteristics and Women's Knowledge of Human Trafficking - Adhikari, Anuska; Shrestha, Bijaya; K.C., Ranju; Nyaupane, Sujata; Karn, Abhishek (Journal of Health Promotion, 2023)
Human trafficking is a serious violation of human rights that disproportionately affects the marginalized individuals, particularly women and girls. This study utilized the data from the 2019 Multiple Indicator Cluster Survey conducted in Nepal to assess the knowledge of currently married women aged 15-49 about human trafficking using a structured questionnaire. The questionnaires were based on the MICS 6 standard questionnaires. The survey used a multistage, stratified cluster probability sampling design and included 14,805 women. In multivariate analysis, respondents in the second to the richest wealth quintiles (aOR range: 1.26-1.56, p